Biological Effects of Ajwa Dates for Pre-Conception Women - Umi Tanzil Fadhila; Ida Royani; Nurfadhillah Khalid (Journal of Community Health Provision, 2026)
Ajwa dates are functional foods that contain bioactive compounds and essential nutrients with potential benefits for women’s reproductive health, particularly during the preconception period. This study aimed to examine the biological effects of Ajwa dates on preconception women, focusing on their nutritional benefits, antioxidant and anti-inflammatory activities, hormonal regulation, ovarian function, and pregnancy readiness. This study used a narrative literature review design based on secondary data obtained from scientific publications published between 2021 and 2026. Data were collected from accredited national journals, reputable international journals, scientific proceedings, and databases such as PubMed, Google Scholar, ScienceDirect, DOAJ, and local open-access journal portals. The selected articles were analyzed using narrative synthesis through thematic organization, comparison between studies, conceptual synthesis, and conclusion drawing. The findings indicate that Ajwa dates contain phenolics, flavonoids, vitamins, minerals, polysaccharides, dietary fiber, and other bioactive compounds that contribute to antioxidant and anti-inflammatory activities. Several studies show that Ajwa dates may help reduce oxidative stress, improve antioxidant defense, modulate inflammatory responses, support hormonal balance, and protect ovarian function, including slowing the decline of Anti-Müllerian Hormone and influencing ovarian follicle characteristics. Ajwa dates also provide nutritional support that may improve women’s physiological readiness before pregnancy.